The Late Precambrian Timna igneous complex, Southern Israel: evidence for comagmatic-type sanukitoid monzodiorite and alkali granite magma - Beyth, Michael; Stern, Robert J.; Altherr, Rainer; Kröner, Alfred (Lithos, 1994)
New data from a geochemical, geochronological and isotopic study of the Late Precambrian Timna igneous complex suggest the formation of alkali granites from a LIL-enriched, mantle derived, sanukitoid-type monzodiorite (a silica oversaturated rock with Mg# >60). These data also provide new insights into the petrology, timing and regional tectonic control of the transition from the calc-alkaline to the alkaline magmatic activity in the northern Arabian-Nubian Shield (ANS) during the Late Precambrian. The Timna alkali granite was formed by fractional crystallization from the monzodioritic magma in a quasi-stratified magmatic cell which formed 610 Ma ago in the 625 Ma old calc-alkaline, porphyritic granite crust. These monzodiorites are mantle-derived, as demonstrated by their high Mg# (63), Cr (230 ppm), and Ni (120 ppm). They are characterized by initial 87Sr86Sr of 0.7034, ϵ-Nd (610 Ma) = +3.4, and are enriched in K2O (2.9%), Sr (840 ppm), Ba (1290 ppm) and LREE [(LaLu)n= 10-25]. The chemical characteristics and REE patterns of the monzodiorites and andesitic dykes of Timna are very similar to Dokhan andesites from northeastern Egypt and the Archean sanukitoids from Canada. The isotopic, geochemical and geochronologic data all indicate that Timna monzodiorites are comagmatic with the alkali granite. The alkali granite is a typical post-orogenic, borderline A-type granite. It is enriched in potassium (K2O=4.68-6.64%), has a negative europium anomaly (EuEu∗=0.058-0.38) and ϵ-Nd (610 Ma) of +3.9. The calc-alkaline granite is a typical I-type granite with a small positive europium anomaly (EuEu∗=1.02-1.16). Its age and the Sr, Nd and Pb isotopic characteristics with ϵ-Nd (625 Ma) of +5.6 to +5.9 are significantly different from these of the alkali granite and monzodiorites, and indicate little interaction with the monzodiorite during the formation of the alkali granite. The alkali granites are correlative with the post-collisional extensional granites in Jordan and Egypt while the porphyritic granites can be correlated with the late orogenic types. Crustal thickening associated with orogenic compression resulted in crustal anatexis to form the I-type granitic rocks, whereas crustal thinning associated with extension allowed LIL-enriched mantle melts to rise very near to the surface, where space was available for these to pond and fractionate to alkali granite.